A Comparative Cost Estimation of Plug and Abandonment Well Using SNI 13-6910-2002 and NORSOK Standard D-010 Regulations: A Case Study in the H-11 Well of Colibri Field - Yusgiantoro, Luky A.; Kristanto, Dedi; Hariyadi, Hariyadi; Stephanie, Vania Raina; Irawan , Gondo (Journal of Petroleum and Geothermal Technology, 2025)
This research discusses the comparative determination of appropriate method for plug and abandonment (P&A) activities in directional wells, and finding an economical cost between SNI 13-6910-2002 and NORSOK Standard D-010 regulations. Colibri field consists of several wells, including H-11 well which is a directional well, where the well was used as a reference for determination in implementation of plug and abandonment activities after the well condition has reached the economic limit. Plug and abandonment (P&A) activities in the Colibri field was implemented with designing a work plan to determine the section for the zone to be plugged by calculating the volume of cement, additives, and completion fluid, using the rig method. The result of the research is to determine the estimation costs that need to be prepared to implement well abandoned activities according to the closing year using SNI 13-6910-2002 and NORSOK Standard D-010 regulations. The cost estimation result of H-11 well using SNI 13-6910-2002 is 417,630.25 USD, while for NORSOK Standard D-010 is 813,315.77 USD. Therefore, based on the cost estimation results, the proposed method chosen for cost estimation of plug and abandoned of H-11 well in Colibri Field is SNI 13-6910-2002 regulation.